Caracterización bromatológica y microbiológica de una vienesa a base de carne de cabra utilizando diferentes formulaciones (60%, 70% y 80%) - Merchán Lapo, María Gabriela (2015)
The present investigation was carried out it in the city of Loja in the Plant Pilot of Meat of The Experimental Fifth it Punctured of the National University of Loja, with the purpose of elaborating to carry out a vienesa using goat meat with different percentages 60% - 70% and 80% and a witness to 0% of goat meat. You elaborates the vienesa with the following treatments of goat meat: T1 (60%); T2 (70%) and T3 (80%), you uses 53 Kg in total (goat meat, pig meat and pig fat) to carry out the formulation, the goat meat obtained it to him in the market of the city of Loja. Once elaborated the product the sensorial evaluation was applied using a scale hedónica of 4 points, to 10 students of the 9no module of the Career Veterinary Medicine and Zootecnia, having a bigger acceptance the treatment from 80% to the same one that was carried out the physical analyses, bromatológic and microbiologic. As a result of the investigation it was determined that the formulation of more acceptability went the T3 to 80%, the results of the physical analysis, bromatológicos and microbiológico you can confirm that the vienesa elaborated with the help of goat meat is capable for its human consumption these values are since inside the limits allowed by the norm INEN of last calidad. For he/she was carried out the cost of production of the three carried out treatments.